Pengaruh Kepadatan yang Berbeda Terhadap Kelulushidupan Dan Pertumbuhan Ikan Nila (Oreochromis niloticus) Pada Sistem Resirkulasi Dengan Filter Arang - Nugroho, Arif; Arini, Endang; Elfitasari, Tita (Journal of Aquaculture Management and Technology, 2013)
Tilapia fish is a commodity freshwater economical. Tilapia relatively easily domesticated and have some lead among the rapid growth, high tolerance for the environment, and resistant to diseases. Fishery cultivation intensive use and dosage dense the weft of which is too high, impacts to decreasing growth and survival rate as well as the water quality. One of the efforts to overcome the problem is with the improvement of the agricultural system through by using charcoal filter in recirculation system. The study was conducted to determine the effect of different densities by using a charcoal filter in the recirculation system on the growth andsurvival rate of tilapia (Oreochromis niloticus). This study was conducted during 40 days of observation, starting from July to October 2012 at the Laboratory of Aquaculture, Diponegoro University, Semarang. Fish sample used is tilapia seed (Oreochromis niloticus) with average zise 4-6 cm. Methods used in this research is completely randomized design (CRD) with 3 treatment and 3 replication. Different dense stocking on every treatment A, B and C, are respectively 10, 15, and 20 tilapia/10 liters which are obsorved in the recirculation system using charcoal filter. The trial diets given with ‘at satiation’ methode 08.00, 12.00, and 16.00 WIB. The result showed density does not affect (P0,05) growth. The used of charcoal filter as a very effective, showed by the low concentration of ammonia in the density 20 tilapia/10 liters until 40 days of observation.